The optimal size of government expenditure in Malaysia - Leslie Balan, anak Lendik (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study aims to examine the optimal level of government expenditure in Malaysia. The analysis consists of annual data for Malaysia ranging from 1975 to 2013. Variables used in this study are gross domestic product, government expenditure and openness index. Results from the unit root tests have indicated that the variables are stationary at first difference. Besides that, the Johansen and Juselius cointegrating test found one long run relationship among the variables used in this study. From the Armey Curve framework, this study has suggested that the optimal level of government expenditure in Malaysia is 13.571%. However, the size of government expenditure ever since the 1997 Asian Financial Crisis exceeded the optimal level found in this study.